2012
DOI: 10.1097/mcg.0b013e318228b781
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Race/Ethnicity on the Clinical Epidemiology of Autoimmune Hepatitis

Abstract: Among AIH patients, Hispanics had the highest prevalence of cirrhosis, and Asians had poorer survival outcomes. Race/ethnicity-specific disparities in AIH epidemiology may reflect underlying genetic differences, contributing to variations in disease severity, response to therapy, and overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 31 publications
6
61
0
6
Order By: Relevance
“…In the current series, NASH was the second leading cause of liver disease in Hispanics with HCC, accounting for 34% of cases. Consistent with prior studies, we found Hispanics demonstrated notable differences in cirrhosis etiologies compared to non-Hispanics, including higher rates of NASH[43,44] and autoimmune cirrhosis[45], and lower incidence of HCV cirrhosis[46]. Additionally, we observed that NASH was particularly prevalent in Hispanic women compared to Hispanic men (72.7% vs 21.9%).…”
Section: Discussionsupporting
confidence: 89%
“…In the current series, NASH was the second leading cause of liver disease in Hispanics with HCC, accounting for 34% of cases. Consistent with prior studies, we found Hispanics demonstrated notable differences in cirrhosis etiologies compared to non-Hispanics, including higher rates of NASH[43,44] and autoimmune cirrhosis[45], and lower incidence of HCV cirrhosis[46]. Additionally, we observed that NASH was particularly prevalent in Hispanic women compared to Hispanic men (72.7% vs 21.9%).…”
Section: Discussionsupporting
confidence: 89%
“…14 Available adult data indicate an incidence varying from 0.67 to 2 cases per 100 000 people. [15][16][17] Ethnic background has been reported as a key factor in clinical presentation and outcomes for patients with AIH 18,19 ; however, this finding is not universal. 20 In the present national study, our primary aim was to determine the incidence of AIH in children and adolescents in Canada and to describe its clinical characteristics and natural history.…”
Section: What This Study Addsmentioning
confidence: 69%
“…And the individuals with Asian background revealed a lower prevalence of liver cirrhosis and a poorer survival outcome compared with the Hispanics. 19 As for the liver function test, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels are increasing constantly or repeatedly, usually reach 3-10 times the upper limit of normal (ULN), and are more significantly increased compared with the changes in bilirubin, alkaline phosphatase (ALP) and γ-glutamyl transpeptidase (γ-GT) levels. The parameters of cholestasis in AIH patients indicate the possibility of overlap syndrome.…”
Section: Clinical Featuresmentioning
confidence: 99%